2015
DOI: 10.1016/j.fertnstert.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of participant retention in infertility treatment trials

Abstract: Objective To identify variables associated with retention (or dropout) in infertility clinical trials. Retention of subjects in randomized controlled clinical trials (RCTs) has received considerable attention, but there have been few consistent findings. Design Secondary analysis of data from RCTs. Setting RCTs conducted by academic medical centers in the U.S. Patients Women with polycystic ovary syndrome or couples with unexplained infertility, 18–39 years of age. Interventions This study is not an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“… 25 , 26 Hormonal contraceptives, selective estrogen receptor modulator (SERM), insulin sensitizers, gonadotropins, and ovarian surgery have been shown to be useful for improving PCOS symptoms in women. 22 , 27 , 28 These treatment approaches address a variety of PCOS symptoms, although current PCOS treatments are not successful in all phases of irregular ovarian function. 22 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 , 26 Hormonal contraceptives, selective estrogen receptor modulator (SERM), insulin sensitizers, gonadotropins, and ovarian surgery have been shown to be useful for improving PCOS symptoms in women. 22 , 27 , 28 These treatment approaches address a variety of PCOS symptoms, although current PCOS treatments are not successful in all phases of irregular ovarian function. 22 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“… 22 , 27 , 28 These treatment approaches address a variety of PCOS symptoms, although current PCOS treatments are not successful in all phases of irregular ovarian function. 22 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Although several studies in other specialties, such as cervical cancer and hypertension research, have examined various strategies to improve retention and adherence to clinical trials in general (Grant and DePew, 1999;Shumaker et al, 2000;Bailey et al, 2004), only a few have evaluated factors that predict retention and adherence in clinical trials including race, ethnicity, socio-economic status and sex, and these have had varying results (Moore, 1997;Gorelick et al, 1998;Bowen et al, 2000). Non-adherence to study protocol in trials involving infertile women may include failure to attend critical study visits, take the assigned medication (McGovern et al, 2008) maintain a prescribed schedule of timed intercourse (Pagidas et al, 2010), and continue participation and follow-up (Kuang et al, 2015). Identifying factors that predict overall non-adherence to study protocol, and the effect of non-adherence upon the primary study outcomes, may help to underscore the importance of adherence, and lead to development of targeted strategies to facilitate adherence to protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Race, ethnicity, BMI, insurance coverage and history of smoking or alcohol use previously have been shown to be predictors of study retention and dropout in Reproductive Medicine Network (RMNs) trials involving women with infertility (Kuang et al, 2015). While medication adherence (McGovern et al, 2008) and intercourse compliance (Pagidas et al, 2010) as individual factors did not affect pregnancy rates, the effect of a composite non-adherence to a study protocol, that includes all these factors, on the outcome of interventional trials in infertile women has not been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%
“… 5 By contrast, clinical studies have found that study engagement and retention are low among underserved populations, including African Americans and individuals without a high school education. 6 , 7 …”
mentioning
confidence: 99%